The Influence of the Service Flower Model on Customer Satisfaction at Restaurants in Dhangadhi - Badal, Mahesh Singh (Journal of NAST College, 2025)
The restaurant industry in Dhangadhi, Nepal, faces increasing competition and evolving customer expectations, necessitating comprehensive service strategies to enhance customer satisfaction. This study investigates the impact of the Flower of Service model, which encompasses core and supplementary services (information, order-taking, hospitality, and exceptions), on customer satisfaction in Dhangadhi’s restaurants. Utilizing a convenience random sampling method, data were collected from 489 restaurant customers through a structured questionnaire employing a 5-point Likert scale. Reliability tests confirmed high internal consistency (Cronbach’s Alpha > 0.89 for all variables). Univariate analysis revealed moderate satisfaction levels across all service elements (mean scores ~3.42–3.51), with exceptions showing the highest variability. Correlation analysis indicated strong positive relationships between customer satisfaction and all service elements, with hospitality exhibiting the highest correlation (r = 0.923). Regression analysis confirmed that order-taking, hospitality, and exceptions significantly influence customer satisfaction, with hospitality being the most impactful (β = 0.53, p < 0.001). Surprisingly, information showed a non-significant effect, suggesting baseline expectations are met. These findings highlight the critical role of hospitality, order-taking, and exception handling in enhancing dining experiences. The study recommends that restaurant managers in Dhangadhi prioritize staff training in hospitality and streamline order-taking processes to foster customer loyalty and strengthen market competitiveness.